Exploring The Impact of Internship Experiences on Students’ Personal and Professional Development Through the Lens of Chickering’s Identity Development Theory - Amin, Umme Umaimah; Nordin, Norhafizi; Hashim, Mohamad Syafiqi; Hasbullah, Siti Aminah (UUM Press, 2023)
The importance of supporting holistic student development has been increasingly recognized in higher education institutions in Malaysia. Hence, this study aims to explore the impact of internship programs on the personal and professional development of Hospitality and Risk Management and Insurance students in Universiti Utara Malaysia. The researchers investigated experience of ten participating students through a small group interview. Utilizing the lens of Arthur Chickering’s Identity Development, the findings related to the seven vectors were analyzed accordingly. Several themes of the internship experiences were identified such as experiences evoke adaption to change, opportunities for personal and professional developments and opportunities for future visioning of a career path. Additionally, a connection exists between the researchers’ findings and Chickering’s seven vectors as the students demonstrated their development along the vectors upon completing the internship. This study provides the benefits of insights into internship students' experiences as they successfully transitioned from dependent learners to autonomous learners. Over time, the desirable outcome for internship students will be achieved, resulting in the inevitable transformation of students into self-directed individuals on their respective life paths.